Rhapsodie d’une voix de la marge ou l’âpre vérité, dans Nulle autre voix de Maïssa Bey - Khedidja Benammar (Multilinguales)
This article focuses on the double punishment suffered by the narrator of Nulle autre voix : a woman, on the margin of the margin because she is a woman and a “criminal” ! The self-righteousness orchestrated by the matriarchy in the name of the patriarchy dictates its sentences and marginalises ad vitam aeternam any transgressor. This study focuses on the one hand on the concept of margin with its spaces of loneliness and on the other on the mechanisms which foster the exhumation of a word from the shadows to it in the folds of writing.